2012
DOI: 10.3389/fpsyg.2012.00066
|View full text |Cite
|
Sign up to set email alerts
|

Shared or Separate Mechanisms for Self-Face and Other-Face Processing? Evidence from Adaptation

Abstract: Evidence that self-face recognition is dissociable from general face recognition has important implications both for models of social cognition and for our understanding of face recognition. In two studies, we examine how adaptation affects the perception of personally familiar faces, and we use a visual adaptation paradigm to investigate whether the neural mechanisms underlying the recognition of one’s own and other faces are shared or separate. In Study 1 we show that the representation of personally familia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 79 publications
(125 reference statements)
2
19
0
Order By: Relevance
“…The adaptation task comprised both within-identity and cross-identity trials. Differently from Rooney et al (2012), they found a transfer of the aftereffect from all adaptor types to all test stimuli, but also a larger magnitude of the aftereffect in the presence of a familiarity match between adaptor and test (e.g. unfamiliar adaptor, unfamiliar test; famous face adaptor, famous face test), except for personally familiar faces (personally familiar faces as adaptors induced smaller aftereffects than other kinds of faces).…”
Section: Familiarity and Face Adaptationmentioning
confidence: 99%
See 3 more Smart Citations
“…The adaptation task comprised both within-identity and cross-identity trials. Differently from Rooney et al (2012), they found a transfer of the aftereffect from all adaptor types to all test stimuli, but also a larger magnitude of the aftereffect in the presence of a familiarity match between adaptor and test (e.g. unfamiliar adaptor, unfamiliar test; famous face adaptor, famous face test), except for personally familiar faces (personally familiar faces as adaptors induced smaller aftereffects than other kinds of faces).…”
Section: Familiarity and Face Adaptationmentioning
confidence: 99%
“…Further studies have shown no effect of familiarity on the magnitude of the aftereffect. Rooney et al (2012) found cross-identity aftereffects characterized by shifts in the perception of attractiveness, normality, and distortedness after exposure to distorted unfamiliar faces, the distorted self-face, and distorted friends' faces. They have interpreted these results as suggesting the existence of a common representation for all classes of faces, regardless of the level of familiarity.…”
Section: Familiarity and Face Adaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-faces and unfamiliar faces involve separate cognitive processing as shown by studies involving visual adaptation (Rooney, Keyes, & Brady, 2012) and gain mechanisms (Keyes & Brady, 2010). Moreover, a unique cortical network for the processing of selfrelated body information, which partially overlaps with a cortical network for the extraction of body-related information (Devue et al, 2007;Hodzic, Muckli, Singer, & Stirn, 2009), has been postulated.…”
Section: Introductionmentioning
confidence: 99%